Injectable tissue integrating networks from recombinant polypeptides with tunable order. Issue 12 (December 2018) - Roberts, Stefan; Harmon, Tyler; Schaal, Jeffrey L.; Miao, Vincent; Li, Kan; Hunt, Andrew; Wen, Yi; Oas, Terrence; Collier, Joel; Pappu, Rohit; Chilkoti, Ashutosh
Abstract Emergent properties of natural biomaterials result from the collective effects of nanoscale interactions among ordered and disordered domains. Here, using recombinant sequence design, we have created a set of partially ordered polypeptides to study emergent hierarchical structures by precisely encoding nanoscale order–disorder interactions. These materials, which combine the stimuli-responsiveness of disordered elastin-like polypeptides and the structural stability of polyalanine helices, are thermally responsive with tunable thermal hysteresis and the ability to reversibly form porous, viscoelastic networks above threshold temperatures. Through coarse-grain simulations, we show that hysteresis arises from physical crosslinking due to mesoscale phase separation of ordered and disordered domains. On injection of partially ordered polypeptides designed to transition at body temperature, they form stable, porous scaffolds that rapidly integrate into surrounding tissue with minimal inflammation and a high degree of vascularization. Sequence-level modulation of structural order and disorder is an untapped principle for the design of functional protein-based biomaterials. A protein-based material with temperature-modulated mechanical properties and function is achieved by the rational incorporation of structural ordering and disordering elements into its polypeptide sequence.